2011
DOI: 10.1016/j.bbabio.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The transmembrane domain 6 of vacuolar H+-pyrophosphatase mediates protein targeting and proton transport

Abstract: Vacuolar H(+)-pyrophosphatase (V-PPase; EC 3.6.1.1) plays a significant role in the maintenance of the pH in cytoplasm and vacuoles via proton translocation from the cytosol to the vacuolar lumen at the expense of PP(i) hydrolysis. The topology of V-PPase as predicted by TopPred II suggests that the catalytic site is putatively located in loop e and exposed to the cytosol. The adjacent transmembrane domain 6 (TM6) is highly conserved and believed to participate in the catalytic function and conformational stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…2a). E301 is highly conserved in plant H + -PPases, and previous mutagenesis studies have shown that mutation of E301 abolishes PPi hydrolysis and proton translocation; for example, E305Q in AVP1 [25] and E301A in VrH + -PPase [26]. We found that the PPi hydrolysis activity of the E301Q mutant was half that of the wild type, and proton pumping activity was undetectable ( Fig.…”
Section: E301q Mutant In Ion Gatesupporting
confidence: 53%
“…2a). E301 is highly conserved in plant H + -PPases, and previous mutagenesis studies have shown that mutation of E301 abolishes PPi hydrolysis and proton translocation; for example, E305Q in AVP1 [25] and E301A in VrH + -PPase [26]. We found that the PPi hydrolysis activity of the E301Q mutant was half that of the wild type, and proton pumping activity was undetectable ( Fig.…”
Section: E301q Mutant In Ion Gatesupporting
confidence: 53%
“…Enzyme Assay and Protein Determination-PP i hydrolysis activity was determined by measuring the release of P i from PP i as delineated previously (7,12,13,26). The reaction medium contained 30 mM Tris/Mes (pH 8.0), 1 mM MgSO 4 , 0.5 mM NaF, 50 mM KCl, 1 mM PP i , 1.5 g/ml gramicidin D, and 20 -30 g/ml microsomal protein.…”
Section: Cloning Expression and Purification Of His-tagged Hmentioning
confidence: 99%
“…The mutated nucleotides were subsequently defined and confirmed by DNA sequencing. The pYVH6 and its relative variants were transformed into the yeast host cell S. cerevisiae strain BJ2168 (MATa, prc-407, prb1-1122, pep4-3, leu2, trp1, ura3, GAL) and cultured according to previous methods (7,12,13). The yeast microsomal membranes enriched in H ϩ -PPases were prepared followed by solubilization and purification with Ni 2ϩ -nitrilotriacetic acid beads as described previously (7,12,13,25).…”
Section: Cloning Expression and Purification Of His-tagged Hmentioning
confidence: 99%
See 1 more Smart Citation
“…2), a residue, which according to site-directed mutagenesis data, is indispensable for ion translocation. [31][32][33][34] The strategic positive charge on the E301 residue facilitates PPi synthesis by stabilizing at the transition state conformation, the negatively charged hydroxyl ion released: Pi 2¡ C Pi 2¡ ! PPi 3¡ C OH ¡ (Step 2; Fig.…”
mentioning
confidence: 99%